Diversity, species composition, ecology and taxonomy of Basidiomycetous macrofungi in forested areas in Central Iloilo, Philippines - Bayona, Leslie Mae C (2023.)
Fungi play a critical role in the decomposition of various substrata in the forest that are essential in maintaining nutrient cycling in this ecosystem. Among these fungi are macrofungal basidiomycetes, among other groups of fungi. Central Iloilo in Western Visayas is one of the regions in the philippines where there is almost no published data on the occurence of this group of microbes. Thus, this study aimed to determine the diversity, composition, and identification of macrofungal species that will serve as baseline information in forested areas in Central Iloilo, Philippines. The sampling was conducted in the forested areas of Barotac Nuevo, Dingle and San Enrique, from October 2020 to January 2021. Each study site was visited three times per month. Opportunistic and purposive sampling was employed in three 1000 m trails. The collected macrofungi were identified through macromorphological and micromorphological characteristics. Results showed a total of 8 orders, 27 families, 53 genera, and 106 morpho species. The majority of the recorder species belong to the Polyporaceae family under Polyporales, represented by 40 species, followed by Marasmiaceae (9 species). Agaricaceae and Mycenaceae with 7 species. The month of November recorded the highest species composition (41.51%) and least in January (15.09%). Among sites, Barotac Nuevo recorded the highest species composition at 47.17% and least in San Enrique (33.02%). In terms of the Shannon-Weiner Index of Diversity, Barotac Nuevo (3.85) had the highest index while San Enrique (3.43) has the lowest index. However, all sites are still considered high diversity sites. The occurrence and distribution of these basidiomycetes were seemingly affected by the type and nature of substrates, vegetation, human interventions, elevation and climatic conditions. The results of this study indicate that these sites still harbor a good number of fungal species and are potential indicators of healthy forest areas in Central Iloilo. This is the first study to document the occurrence of macrofungal basidiomycetes in Central Iloilo, Philippines.
Thesis (M.S. Biology) -- Miagao, Iloilo : University of the Philippines Visayas, January 2023.